(untitled) (Malaysian Journal of Learning and Instruction, 2010)
Purpose – The application of asynchronous mode of computermediated communication such as the online discussion forum is becoming more prevalent in our learning environment. Online forum is important for learning to take place as it allows the creation of a "virtual community of inquiry" that encourages problem solving, critical thinking, and knowledge construction. Thus, this study sought to analyse the content of trainee teachers’ discussion in an online forum, especially in terms of their critical thinking levels. An online discussion forum was created for the trainee teachers to discuss their experience and problems encountered during the teaching practicum. Method – A total of 30 Universiti Sains Malaysia pre-service teachers who underwent 20 weeks of teaching practice in secondary schools were involved in this study. The Newman, Webb and Cochrane (1995) framework was used to analyse the students’ levels of critical thinking skills as indicated in their messages or reflections. The depth of the their critical thinking in terms of relevance, importance, novelty, accuracy, linking ideas or interpretation, justification, critical assessment, and practical utility were of interest in this study. Findings – Throughout the 20 weeks of teaching practice, a total of 896 positive critical thinking indicators were recorded from the participants’ discussion. Their reflections focused mainly on the aspects of relevance, importance, and justification of the issues being discussed. However, the trainees hardly tried to bring outside knowledge or experience to address problems, and their input barely refl ected their width of understanding in discussing the issues. The online discussion forum, nevertheless, has provided a platform for the trainees to share and reflect their problems during the teaching practicum session. 76 Value – The paper explores the potential of an online discussion forum to be applied during teacher practice session. Based on these findings, it is recommended that our teacher training institutions integrate this technology into their curriculum.